Incidencia de los acentos dialectales en la comprensión auditiva de los estudiantes del programa aprendizaje de idioma extranjero – inglés de la Universidad Técnica de Cotopaxi. - Collaguazo Vega, Wilmer Patricio (2017)
The present research entitled "Incidence of dialect accents in the listening comprehension of students into the Learning Foreign Language Program – English at the Technical University of Cotopaxi", addresses the importance of integrating the practice of pronunciation and comprehension of different dialect accents, in the process of teaching the English language, for the development of oral expression in the students of the English Language Teaching Program at the Technical University of Cotopaxi in the semester March to August of this year, 2017. The design of the research model is non-experimental, i.e., no measurement variables were used if one takes into account that its main purpose is to describe the problem and give it a solution. Field research included the application of information gathering techniques, including the survey and an auditory discrimination test, which allowed the evaluation of the level of development of communicative competence in English language learners as well as the level of use of dialect accents in listening comprehension. Statistical analysis and processing of the obtained information was performed for the interpretation of results. Finally, it is proposed the design of a Manual of metacognitive strategies based on the teaching of dialect accents that will contribute to the development of communicative competence in students.